Saudi Arabia : 2016 Article IV Consultation-Press Release; Staff Report; and Informational Annex. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that real GDP growth in Saudi Arabia is expected to slow to 1.2 percent in 2016, but recover to 2 percent in 2017 as the pace of fiscal consolidation eases. Inflation has risen in recent months to more than 4 percent owing to increase in energy and water prices. Bank deposits have declined, but growth of credit to the private sector remains strong. Capital buffers are high, nonperforming loans low, and banks are well provisioned against loan losses. The current account deficit is projected to narrow to 6.4 percent of GDP in 2016 and then move close to balance by 2021 as oil prices partial recover.